Transforming the Role of Guidance Counselors as Anti-Bullying Agents through Case-Based Learning (3C3R) Basic Service Training - Yosef Yosef; Khadijah Lubis; Alrefi Alrefi; Nur Wisma; Anisa Siti Nurjanah; Muhammad Bagas Putra Pratama; Ramadhan Ramadhan (International Journal of Public Devotion, 2026)
Indonesia, as a multicultural country, faces a major challenge in preventing bullying practices rooted in cultural differences in educational environments. With the spread of bullying practices in Indonesia, guidance and counseling teachers (BK) need to be equipped with the understanding and skills to provide services to students, including basic case-based services. This activity was carried out at SMAN South Sumatra, attended by 23 BK teachers who are members of MGBK SMA Kota Palembang. The activity was carried out in October to November 2025 in a hybrid manner. The activity was conducted using discussion, practice, case-based learning, and assignment methods, where participants were trained to create cases and solve them using 3C3R. The activity began with a pretest, followed by material delivery, practice, mentoring, and ended with a posttest. The output of this training is the preparation of RPL and  multicultural bullying case which will be applied to basic services.  The analysis of pretest and posttest data showed an N-Gain coefficient of 0.85, which is in the high category. This indicates an increase in the understanding and skills of guidance counselors in implementing basic case-based services to enhance students' multicultural awareness. This training was effective in improving the competence of guidance counselors as agents of multicultural bullying prevention and supporting the creation of an inclusive and harmonious school environment.Transformasi Peran Guru BK sebagai Agen Antibullying melalui Pelatihan Layanan Dasar Berbasis Case-Based Learning (3C3R)ABSTRAKIndonesia sebagai negara multikultural menghadapi tantangan besar dalam mencegah praktik bullying yang berakar dari perbedaan budaya di lingkungan pendidikan. Semakin meluasnya praktik bullying di Indonesia, guru bimbingan dan konseling (BK) perlu dibekali pemahaman dan kemampuan untuk memberi layanan kepada siswa termasuk layanan dasar berbasis kasus. Kegiatan ini dilakukan di SMAN Sumatera Selatan yang diikuti oleh 23 guru BK dan merupakan anggota MGBK SMA Kota Palembang. Kegiatan dilaksanakan pada bulan Oktober sampai November 2025 secara hybrid. Pelaksanaan kegiatan dilakukan dengan metode diskusi, praktik, case based learning, dan penugasan, dimana peserta dilatih untuk membuat kasus dan menyelesaikan kasus tersebut menggunakan 3C3R. kegiatan diawali dengan pengisian pretest, pemberian materi, praktik, pendampingan dan diakhiri dengan pengisian posttest. Output dari pelatihan ini berupa penyusunan 1 RPL dan 1 Kasus bullying multikultural yang akan diterapkan pada layanan dasar. Hasil analisis data pretest dan posttest menunjukkan nilai koefisien N-Gain sebesar 0,85 dan berada pada kategori tinggi. Hal ini menunjukkan pelatihan ini efektif dalam meningkatkan kompetensi guru BK sebagai agen pencegahan bullying multikultural dan mendukung terwujudnya lingkungan sekolah yang inklusif dan harmonis. Kata Kunci :Layanan Dasar; Case Based Learning; Guru BK; Bullying Multikultural; Pendidikan Multikultural